Library staff members. - Unknown:::Creator::::::::::::
Written on verso: "Library staff members; The date was that of E. Evans graduation; Eliot Arthur Powel Evans (student assistant), C H Bailey; J Backus; J B Jackson; H Bailer; Marie Waiburton; Frances Hichborn; Olive Slocum."